Calcitonin gene-related peptide antagonists in pregnancy: a disproportionality analysis in VigiBase - Noseda, Roberta; Bedussi, Francesca; Gobbi, Claudio; Ceschi, Alessandro; Zecca, Chiara (Journal of headache and pain, 2024)
Background Current evidence on the safety of calcitonin gene–related peptide antagonists (CGRP-A) in pregnancy for the treatment of both episodic and chronic migraine is scarce and does not yet provide definitive information. By querying VigiBase ® , the World Health Organization global pharmacovigilance database, this study aimed to detect differences in the reporting frequency between CGRP-A and triptans in relation to pregnancy. Methods Disproportionality analyses on de-duplicated safety reports collected in VigiBase ® as of 31.05.2023 reporting exposure to CGRP-A in pregnancy with or without pregnancy outcomes. A Reporting Odds Ratio (ROR) with a 95% confidence interval (CI) was used as a measure of disproportionality and the threshold for the detection of a signal of disproportionate reporting was set with a 95% CI lower limit > 1. Findings Four hundred sixty-seven safety reports reported exposure to CGRP-A in pregnancy, mostly originating from the United States of America (360/467, 77%), more frequently reported by patients (225/467, 48%), who were mainly females (431/467, 92%), and more frequently reported exposure to CGRP-A during pregnancy (400/467, 86%). Compared to triptans, no signals of disproportionate reporting were detected with CGRP-A either for the overall reporting of pregnancy-related safety reports (ROR 0.91, 95% CI 0.78–1.06), for the reporting of pregnancy outcomes (maternal and/or foetal/neonatal, ROR 0.54, 95% CI 0.45–0.66), or for the reporting of foetal/neonatal outcomes (ROR 0.53, 95% CI 0.41–0.68). Conclusions This study showed that, to date, there are no signals of increased reporting with CGRP-A compared to triptans in relation to pregnancy in VigiBase ® . Future pharmacovigilance studies are needed to confirm these findings.